Multidimensional poverty as a constraint on human development in the community of 28 de Marzo of Santa Inés, estado Lara, Venezuela (Mayéutica Revista Científica de Humanidades y Artes, 2024)
The present investigation described the levels of multidimensional poverty and its implications for Human Development in the households of the Sector 28 de Marzo of the community of Santa Inés, municipio Urdaneta, estado Lara during the firstsemester of 2022. The study was carried out from the quantitative paradigm, basing in the methodology of multidimensional poverty of Alkire and Foster and some theories of the human development. Locating in the line of research Sustainability, equity and participation of the Desarrollo Humano program of the Decanato Experimental de Humanidades y Artes of the Universidad Centroccidental Lisandro Alvarado. The study population consisted of 105 homes in the 28 de Marzo sector and the sample was 87 houses. The instrument was a questionnaire of 18 articles, and 95% reliability was calculated. As a data analysis technique,descriptive statistics were extracted through the frequency distribution. Among the results obtained, from the dimensions addressed health, work, education, conditions of childhood and youth, it was evidenced that there is a high level of deprivation related to multidimensional poverty, such as the precarious conditions in health, urban cleanliness, water and mobile telephony, which affect the adequate development of their capabilities.
Keywords: Multidimensional Poverty; Human Development; health; education; public services; Alkire, S. (2016). The Global Multidimensional Poverty Index (MPI): 5year methodological note. The Oxford Poverty and Human Development Initiative. (OPHI). https://www.ophi.org.uk/wpcontent/uploads/MPI_Methodology_2010 2015_Jan2016.pdf Feres, J.C. y Mancero, X. (2001). El método de las Necesidades Básicas Insatisfechas (NBI) y sus aplicaciones en América Latina. División de Estadística y Proyecciones Económicas. CEPAL. Serie: estudios estadísticos. Programa de Naciones Unidas para el Desarrollo. (1990). Informe de desarrollo humano. Tercer Mundo Editores. http://hdr.undp.org/sites/default/files/hdr_1990_es_completo_nostats.pdf Programa de las Naciones Unidas para el Desarrollo. (2010). Informe de desarrollo humano. Edición del Vigésimo Aniversario. https://hdr.undp.org/sites/default/files/hdr_2010_es_complete_reprint.pdf Sen, A. (2000). Desarrollo y libertad. Editorial Planeta.